European climate targets achievable without nuclear power - Claudia Kemfert; Clemens Gerbaulet; Christian von Hirschhausen; Casimir Lorenz; Felix Reitz (DIW Economic Bulletin, 2015)
The upcoming Climate Change Conference in Paris will once again highlight the need for action to reduce global greenhouse gas emissions in order to mitigate climate change. The relevant global energy scenarios are often still based on the assumption that the expansion of nuclear power can contribute to climate change mitigation. The spiraling investment and operating costs of nuclear plants, the unresolved issues concerning the dismantling of these plants and permanent storage of nuclear waste, and the continuing lack of insurability against nuclear accidents make nuclear power extremely unattractive from an economic perspective. As a result, many nuclear power companies are facing financial difficulties. The nuclear renaissance was simply a fairy tale: the majority of the around 400 nuclear power stations currently in operation around the world are outdated and will still need to be dismantled after they have been decommissioned. The construction of new nuclear power plants is restricted to a small number of countries, predominantly China. DIW Berlin has modeled a number of scenarios to forecast European power supply up to 2050 and these show that, with a marked expansion of renewable energy sources, Europe can meet its climate targets without nuclear power. The proliferation of more cost-effective renewable energy technologies, particularly wind and solar power, can compensate for the anticipated decline in nuclear power. In a scenario that includes no new nuclear power plant construction at all, renewables account for 88 percent of powergeneration capacity. Nuclear power was not, is not, and never will be a sustainable energy source and is, therefore, unsuitable for an efficient climate policy. A transition to greater use of renewables is the more cost-effective option overall.
Keywords: L95; L51; Q41; 330; nuclear energy; electricity; modeling